107 Effect of semen extender and storage temperature on ram sperm motility over time. (1st February 2016) - Acharya, M.; Burke, J. M.; Smyth, E.; Davis, A.; Lester, T. D.; Rorie, R. W.
Abstract: Viability of stored chilled extended semen from rams is dependent on factors such as type of extender and storage temperature. The objective was to determine the effect of semen extender and storage temperature on motility of ram semen for up to 72 h. Semen with at least 35% motile sperm was collected by electroejaculation from 3 mature and 2 yearling Katahdin rams. Each semen collection was extended using four different extenders: milk (Mi), Tris-citrate (Tc), Tes-tris (Tt), and sodium-free (CJ2). Semen was diluted to 600 million sperm/mL and loaded into 0.25-mL straws for storage at 4°C or 15°C. All extenders were supplemented with 5% egg yolk. Percentage motile (path velocity ≥ 30 µm/sec and progressive velocity ≥ 15 µm/sec) and progressive (path velocity ≥ 50 µm/sec and straightness ≥ 70%) sperm were determined at 0, 24, 48, and 72 h of storage using computer-assisted system analysis. Data were analyzed using the PROC MIXED procedure of SAS, with semen collection as the experimental unit. Variables in the model included extenders, temperatures, hour (repeated measures) and interactions. Percentage motile sperm decreased ( P < 0.01) over time, regardless of extender. The decrease in motile ( P = 0.36) and progressive sperm ( P = 0.26) motility was similar between storage temperatures. Sperm motility was greater ( P < 0.05) in Tc (49.5 ± 2.7%) than other extenders, but similar ( P > 0.05) between Tt (39 ± 2.7%) and Mi (34.8 ± 2.7%). Sperm in Tt extender had greater motility ( P < 0.05) than those in CJ2 (27.4 ± 2.7%). There was an extender by storage time interaction ( P < 0.01), with sperm motility declining more rapidly in CJ2 than in other extenders. Within 24 h, percentage of progressively motile sperm decreased ( P < 0.01) from a mean of 35.2 ± 1.0% to a mean of 8.6 ± 1.0%. Between 24 and 72 h, percentage of progressively motile sperm decreased ( P < 0.01) to 3.3 ± 1.0%. Decrease in progressive motility was observed across all extenders. Results indicated that progressive motility of ram sperm is greatly reduced within 24 h or storage, regardless of extender or storage temperature.